Mewujudkan Perilaku Kolekstif;: Pengembangan Pendidikan Akhlak di Kelas dalam Perspektif â€œPilihan Rasionalâ€ - Asrohah, Hanun (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
Islamic education aims to establish students` moral, which should be developed in the classroom. Students` behavior is determined by values that understood and maintained together through interaction in the class. Various perspectives on human behavior and actions have been discoursed by experts of Islamic theology, Muslim philosophers, and other scholars, such as al-Mawardi and IbnTaymiyya. This paper will discuss the perspective of Rational Choice in Sociology of Education about the formation of the learners` behavior. According to Rational choice, classroom learning is the accumulation of the goal. Various actions of learners in learning are not only determined by the purpose of learning, but also other purposes, such as the objectives of individual learners. Learners in the class action are also based on the consideration of uses, such as to get high scores or praise. In learning, achievement of learning objectives depends on the ability of learners which lead to a probability, such as the possibility of getting high or low value. Learning is based on rational purpose and usefulness in accordance with the purpose of education, will lead to satisfactory academic results. The individual rational action depends on the perception and recognition of learners. The action was carried out together in the classroom and together will form the desired pattern of actions and behavior. The pattern of actions and behaviors can escalate into patterns of values and morality in relationships in the classroom. Thus, the rational choice theory can be used as the basis of formation of character in a class that is also a reflection of the wider community.